Meningkatkan Kemampuan Berhitung Menggunakan Pendekatan Realistic Mathematic Education (RME) bagi Anak Diskalkulia - Zelinda, Erva; Fatmawati, Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2022)
The Discussion In this research is about increasing numeracy skills using the Realistic Mathematical Education (RME) approach at SD Negeri 33 Gurun Panjang. Subjects in this study were class two dyscalculia children from SD Negeri 33 Gurun Panjang. In  this research we have adopted a Single Subject Research method and the A-B-A design is used in this experimental research. Baseline (A1), intervention (B), and baseline (A2) include the name of the design A–B-A. Data collection in this study was done using tests. Results of the survey were analyzed using visual analysis techniques using graphs. After being given an intervention using the Realistic Mathematics Education (RME) approach on research, was described capacity of add up children with dyscalculia increased. Conclusion can be drawn in this research that computational ability of dyscalculia children can increase using the Realistic Mathematical Education (RME) approach.